2019
DOI: 10.1038/s41389-019-0161-z
|View full text |Cite
|
Sign up to set email alerts
|

UVB-induced DHODH upregulation, which is driven by STAT3, is a promising target for chemoprevention and combination therapy of photocarcinogenesis

Abstract: The leading cause of cutaneous squamous cell carcinomas (cSCCs) is exposure to ultraviolet radiation (UV). Unlike most other cancers, the incidence rates of cSCCs are still on the rise and the treatment options currently available are limited. We have recently found that dihydroorotate dehydrogenase (DHODH), which is the rate-limiting enzyme in the de novo pyrimidine synthesis pathway, plays a critical role in UVB-induced energy metabolism reprogramming. Using a multistage model of UVB radiation-induced skin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Additionally, enhanced activity of DHODH has been implicated as a biomarker of malignant tumor including gastric cancer and skin cancer 15 , 16 . Ultraviolet radiation could transcriptionally induce DHODH expression by activating STAT3 17 . Inhibition of DHODH leads to the starvation of pyrimidine pool and thereby decreases DNA and RNA synthesis and cell proliferation 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, enhanced activity of DHODH has been implicated as a biomarker of malignant tumor including gastric cancer and skin cancer 15 , 16 . Ultraviolet radiation could transcriptionally induce DHODH expression by activating STAT3 17 . Inhibition of DHODH leads to the starvation of pyrimidine pool and thereby decreases DNA and RNA synthesis and cell proliferation 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…DHODH blockade could be significant in the prevention or therapy of nonmelanoma skin cancers and possibly other hyperproliferative keratinocytic diseases [ 85 ]. Chronic inhibition of DHODH by leflunomide blocks UVB-induced cutaneous SCC initiation [ 87 ]. Moreover, it is found that BRQ and doxorubicin synergistically inhibited melanoma xenografts [ 88 ], and this combination significantly downregulated cell cycle regulatory proteins, cyclin B1, and upregulated its binding partner pcdc-2 and p21 [ 88 ].…”
Section: The Various Malignances and Dhodhmentioning
confidence: 99%
“…As gemcitabine treatment leads to increased de novo pyrimidine synthesis in pancreatic cancer cells, combination of DHODH inhibitor Ter with gemcitabine reversed gemcitabine-induced nucleoside synthesis and thus exhibits synergistic effect against pancreatic cancer proliferation [ 82 ]. Furthermore, teriflunomide combined with the genotoxic agents such as 5-fluorouracil (5-FU) [ 87 ], melphalan, treosulfan, doxorubicin, dexamethasone, and bortezomib reveal the synergistic and additive activity in multiple myeloma [ 65 ] and UVB-induced cSCC [ 87 ] proliferation suppression. Combination treatment of BRQ and doxorubicin results in significant anti-proliferation effects on melanoma cells both in vitro and in vivo [ 88 ].…”
Section: Prospects Of Dhodh Inhibitors In Cancer Therapymentioning
confidence: 99%
“…Despite the failure of brequinar in past clinical studies, recent publications renewed interest in DHODH as a target in cancer therapy and both old and recent series of DHODH inhibitors were shown to have promising antitumor properties. This was demonstrated in various in vivo models when administered alone or in combination with other drugs, in particular in acute myeloid leukemia (AML), neuroblastoma, PTEN (Phosphatase and TENsin homolog) mutant triple negative breast cancer cells, and KRAS (V-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog) mutant pancreatic cancer cells [5][6][7][8][9][10][11][12][13][14]. Several DHODH inhibitors, including brequinar, leflunomide and new molecules such as BAY2402234 or PTC299, are currently being evaluated in clinical trials for cancer therapy [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its cytostatic effects, DHODH inhibition is known to have a strong impact on gene expression, cell metabolism, and differentiation [5,12,14,15,28]. Our team is interested in the existing relationships between pyrimidine biosynthesis and the activation of innate immunity, with a specific focus on the interferon (IFN) response.…”
Section: Introductionmentioning
confidence: 99%